Prevalence and predictors of transitions to and away from syringe exchange use over time in 3 US cities with varied syringe dispensing policies. - Green, Traci C; Bluthenthal, Ricky N; Singer, Merrill; Beletsky, Leo; Grau, Lauretta E; Marshall, Patricia; Heimer, Robert (Drug and alcohol dependence, 2010)
Syringe exchange programs (SEPs) can reduce HIV risk among injecting drug users (IDUs) but their use may depend heavily on contextual factors such as local syringe policies. The frequency and predictors of transitioning over time to and from direct, indirect, and non-use of SEPs are unknown. We sought, over one year, to: (1) quantify and characterize transition probabilities of SEP attendance typologies; (2) identify factors associated with (a) change in typology, and (b) becoming and maintaining Direct SEP use; and (3) quantify and characterize transition probabilities of SEP attendance before and after changes in policy designed to increase access. Using data collected from 583 IDUs participating in a three-city cohort study of SEPs, we conducted a latent transition analysis and multinomial regressions. Three typologies were detected: Direct SEP users, Indirect SEP users and Isolated IDUs. Transitions to Direct SEP use were most prevalent. Factors associated with becoming or maintaining Direct SEP use were female sex, Latino ethnicity, fewer injections per syringe, homelessness, recruitment city, injecting speedballs (cocaine and heroin), and police contact involving drug paraphernalia possession. Similar factors influenced transitions in the syringe policy change analysis. Policy change cities experienced an increase in Indirect SEP users (43-51%) with little increased direct use (29-31%). We found that, over time, IDUs tended to become Direct SEP users. Policies improving syringe availability influenced SEP use by increasing secondary syringe exchange. Interactions with police around drug paraphernalia may encourage SEP use for some IDUs and may provide opportunities for other health interventions.
Keywords: Adult; Cities; Female; HIV Infections; Humans; Longitudinal Studies; Male; Middle Aged; Needle Sharing; Needle-Exchange Programs; Odds Ratio; Prevalence; Public Policy; Regression Analysis; Substance Abuse, Intravenous; United States